The influence of religious faith on prosocial intentions and behaviors. Findings from a cross-sectional survey among young adults voluntarily working in social contexts - Büssing, Arndt (Forum Pedagogiczne, 2024)
Despite the constant decline of religious trust in Western societies, young adults are still voluntarily working in a social context. Nevertheless, Living from Faith / Being with God (as a religious orientation in life) was of relevance for only about one-third of these young adults. They scored higher on this source of faith when they were raised in a religious family and were active members of a church community, indicating that religious socialization is relevant for their formation of faith and related ethics and ideals. However, in this sample of young adults, all were voluntarily engaged in the social field, whether they were active in their church, had a specific faith as an orientation in their life, and believed in God or not. Concerning compassion as an intention and their commitment to disadvantaged people, Living from Faith / Being with God was less relevant as compared to the ability to pause in wondering awe with subsequent feelings of gratitude. This does not mean that religious faith would be less relevant, as intrinsic religiosity aims to reconnect with the Sacred. It is thus an end in itself, rather than a tool to obtain something (Allport & Ross, 1967). Both resources could be further trained and developed, as compassion, awe, and gratitude are self-transcendent emotions that are relevant for a society that has to respond to global crises, rapid culture shifts, and thus growing anxiety and insecurity.